Analisis Kepatuhan Investasi Aset Kripto terhadap Prinsip-Prinsip Hukum Ekonomi Syariah di Indonesia - Abrada Ali Ismail Tarigan; Zulpahmi Lubis (Verdict: Journal of Law Science, 2026)
Crypto asset investment has become a prominent form of modern muamalah (social dealings) that is increasingly favored by the Indonesian public, particularly among the youth demographic aged 20–35. Within the world’s largest Muslim population, integrating investment activities with Sharia values has become an important issue for religious and financial institutions. This study aims to analyze the level of Sharia compliance in crypto asset investment and identify internal and external factors influencing it, particularly regarding transparency (shafāfiyyah), understanding of contracts (akad), and potential gharar (uncertainty) in digital transactions. This research employs a qualitative method with a juridical normative approach through literature study, examining scientific journals, books, DSN-MUI fatwas, and Bappebti regulations related to crypto asset trading in Indonesia. The findings show that Sharia compliance depends on the transparency of information, clarity of underlying assets, validity of akad, and investors’ understanding of transaction mechanisms. Although blockchain technology provides transparency and accountability, limited financial and Sharia literacy may still create gharar fi al-ma’lūm due to inadequate understanding of asset characteristics and contractual structures. External factors, including government regulations, institutional supervision, and religious guidance, also significantly influence the alignment of crypto investment practices with Sharia principles. This study concludes that crypto assets cannot be universally categorized as halal or haram but require case-by-case evaluation based on asset structure, transaction mechanisms, objectives, and socio-economic impacts. Strengthening regulation, literacy, and Sharia compliance mechanisms is essential to achieve maqāṣid al-syarī‘ah values, particularly justice (‘adl), protection of wealth (ḥifẓ al-māl), transparency, and maslahah.